Opportunities for Increasing Efficiency by Public Utility Organizations - Kocziszky, György; Somosi, Mariann Veresné (European Journal of Economics and Business Studies, 2017)
The result and expenditure based performance measurement and evaluation are much the same age in the private sector with the modern enterprise theory. It is enough to make an overview of the Anglo-Saxon and German literature between the two world wars, which pays significant attention on the economic and work organizational tools and methods of enterprise level performance measurement and improvement. The public sphere and within this the issue of operational and economic efficiency measurement of public utility organizations has got a more modest past and methodological framework, although its significance is not smaller. The authors in their research make an attempt to compensate it, when they make suggestions for the performance evaluation process and methods of public utility organizations.